Challenges and Strategies in the Implementation of Sexual Violence Prevention and Response Task Forces in Religious Higher Education Institutions in Indonesia - Akhmad Anwar Dani; Fathan Fathan; Budiasih Budiasih; Danang Try Purnomo; Ni Putu Eka Merliana (UIN Sunan Gunung Djati, 2025)
This study aims to analyze the challenges and strategies in enhancing the effectiveness of sexual violence prevention and response task forces in Indonesian religious higher education institutions. The study identifies various obstacles that universities face in implementing policies for the prevention and handling of sexual violence, as well as the strategies they employ to overcome these challenges. This research adopts a qualitative approach, collecting data through in-depth interviews and Focus Group Discussions (FGD) with heads of gender and child study centers, members of the sexual violence prevention and response task forces, and lecturers across seven religious higher education institutions in Indonesia. The findings reveal that, although several universities have established task forces, they still encounter major challenges, such as limited trained human resources, victims’ reluctance to report incidents, and conservative campus cultures. However, the strategies implemented, including continuous training for staff and lecturers and the use of technology for reporting, have proven effective in raising awareness and improving responsiveness to sexual violence. This study contributes significantly to the development of policies for the prevention and handling of sexual violence in religious higher education institutions. It recommends strengthening institutional structures, intensifying training programs, and developing more integrated digital reporting systems to create safer and more responsive campuses. Furthermore, this research provides an original contribution by exploring the challenges and strategies faced by religious universities in implementing sexual violence prevention and response policies, offering new insights into how these strategies can be improved and adapted to the specific context of religious higher education in Indonesia.